Functional spectroscopic imaging reveals specificity of glutamate response in mouse brain to peripheral sensory stimulation - Seuwen, Aline; Schroeter, Aileen; Grandjean, Joanes; Schlegel, Felix; Rudin, Markus (Scientific reports, 2019)
Non-invasive investigation of physiological changes and metabolic events associated with brain activity in mice constitutes a major challenge. Conventionally, fMRI assesses neuronal activity by evaluating activity-evoked local changes in blood oxygenation levels (BOLD). In isoflurane-anaethetized mice, however, we found that BOLD signal changes during paw stimulation appear to be dominated by arousal responses even when using innocuous stimuli. Widespread responses involving both hemispheres have been observed in response to unilateral stimulation. MRS allows probing metabolic changes associated with neuronal activation and provides a complementary readout to BOLD fMRI for investigating brain activity. In this study we evaluated the sensitivity of a free induction decay (FID) based spectroscopic imaging (MRSI) protocol for the measurement of alterations in glutamate levels elicited by unilateral electrical paw stimulation at different current amplitudes. Coronal MRSI maps of glutamate distribution with 17 × 17 voxels of 1 µl volume have been recorded with a temporal resolution of 12 min. Significant region-specific increases in glutamate levels have been observed in the contralateral but not in the ispiateral S1 somatosensory cortex upon stimulation. The amplitude of glutamate changes increased in a dose-dependent manner with the stimulus amplitude. The study demonstrates feasibility of functional MRSI in mice for studying activity-evoked glutamate changes in a temporo-spatially resolved manner.